The role of technical and vocational education towards Fourth Industrial Revolution in preparing workforce in Malaysia - Jusoh, Rosnani; Mohd Puad, Mohd Hazwan; Jamaluddin, Rahimah; Ismail, Normala (RSIS International, 2024)
Technical and Vocational Education (TVET) is an engine of socialand economic development of the country in meetingthe needs of fourth(4.0) industrial revelution. Therefore,TVET field is perceived to play a role in providing an adequate competencies workforce for the industrial revolution 4.0. This is because the industrial revolution 4.0 has become more valuable in today’s world due to the economic and social benefits provided especially in the field of production. The objective of this paper is to investigate the role of technical and vocational education towards industrial revolution 4.0 in preparingworkforce in Malaysia through literature review and previous study related to the topic. These inquiries provide a comprehensive understanding, establishing a robust theoretical foundation for this paper. This study used a comprehensive review of existing literature and empirical evidence. We will examine the various ways in which Technical and Vocational Education (TVET)fosters the knowledge and skills to prepare the nation workforce in industrial revolution 4.0.The literature review plays a pivotal role in this study, involving the meticulous identification and synthesis of pertinent research findings. To ensure comprehensive coverage, the researchers employed various search strategies, including leveraging search engines such as Google Scholar and accessing online journals. Key search terms such as Technical and Vocational Education, Industrial Revolution 4.0 in providing workforce in Malaysia were utilized to retrieve relevant articles and studies.A thorough analysis and comparison of established theories and models on Educational Readiness Model for Industrial Revolution 4.0 were conducted, with particular emphasis on their intersection with theories related to providing workforce. This integrative approach provided valuable insights, perspectives, and recommendations pertaining to the practical implementation and advancement of development TVET within educational institutions worldwide.In the 21st century, the success of an organization does not only depend on the products and services offered, but also on the workforce provided. This study concludes Industry 4.0 or also known as 'smart manufacturing' or 'internet industrialization'.The manufacturing industry has been transformed into a fourth revolution that is expected to affect the entire industry by changing the way goods are designed, produced, delivered, paid for and used. Therefore, education needs to pay attention, especially PTV.